Human Rights, Gender, and Science in the Perspective of Maqāṣid Sharī’ah - Nur, Iffatin; Fithriy, Haniefa Nuruddienil; Ilmas, Divia Nur Alan Nur; Wakhid, Ali Abdul (Analisis: Jurnal Studi Keislaman, 2023)
Gender, human rights, and the advancement of science and technology with all their problems are some interesting and highly discussed contemporary issues, especially when they are related to Islamic teachings. This is inseparable from some people’s lack of understanding of Islamic teachings and baseless accusations of Islam as being old-fashioned on such contemporary issues. So, the basic question is how Islam views these issues. This study is library research with data analyzed using the maqāshid sharī’ah (objectives of Islamic law) approach. The findings of this study indicate that Islam upholds human rights; places gender issues proportionally while guaranteeing the dignity of each gender without discrimination, and encourages humans to develop, promote, and utilize science and technology as much as possible while still referring to moral reasoning in its utilization.